A proposed development plan for the Church of the Risen Lord (CRL) Library at the University of the Philippines Diliman - Tayam, Tiana Rose Norfi N.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
With the aim of contributing to the existing research literature of church libraries, this study examined the Church of the Risen Lord (CRL), an interdenominational Christian community located inside the University of the Philippines Diliman, and proposed a development plan for the church’s library.

Quantitative and qualitative approach was used to analyse the information needs, considering factors such as resources and services, the library collection, the management and organization, and current status, in terms of facilities and financial aspects, to develop the church library. A total of 69 respondents answered the printed and online survey questionnaires. Interviews with the coordinator of the library and the pastor were done separately in order to address the financial and management and staffing factor. Answers from two focus groups, the CRL members and the potential users, were evaluated using coding method and interpreted.

The study revealed that potential users of the church library were mostly younger than 30 years old, female, single, students, achieved higher education, and literate. English is the preferred language and most respondents were interested in reading and they stated to have read every day. The church library collection should contain books mostly on the following topics: books on Psychology and Sociology, materials with a multicultural and feminist viewpoint, and books on Christianity, culture, and current issues. The church library should have teaching aids and journals and also be able to provide documentation whether in print or in audio or video recordings of Sunday sermons, devotionals and similar discourses. Moreover, the church library should be capable to provide a guide to the online and electronic resources. Clear policies on donations must be implemented. The study revealed that the recommended organizational structure and library administration by McMichael (1987) is applicable to the church library with some revisions. Library services and service hours would be the same as other libraries.
Thesis (Bachelor of Library and Information Science)
Keywords: Church of the Risen Lord Library; Development plan